ANALISIS PENGARUH KEMISKINAN DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI BANTEN PADA TAHUN 2018-2021 - Syadina Khumaerah, Ayyissilla (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The Human Development Index (HDI) is a comparative measure of life expectancy, literacy, education and standard of living. HDI explains how the population can access development outcomes in obtaining income, health, education, and so on.but in Indonesia even in Banten itself it is not spared from problems such as poverty and unemployment. The purpose of this study is to analyze how and how much poverty and open unemployment rates affect the human development index in provincial districts and cities in the period from 2018 to 2021. This research uses quantitative research using panel data method.The purpose of this study is to analyze how and how much poverty and open unemployment rates affect the human development index in provincial districts and cities in the period from 2018 to 2021. This research uses quantitative research using panel data method.